2012
DOI: 10.1002/biof.1001
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of evidence: Carotenoids and other micronutrients in the prevention and treatment of cognitive impairment

Abstract: Cognitive impairment is a common age-related disorder which affects in the stadium and type Alzheimer's Disease (AD) a steadily growing number of patients. AD is not curable and is not being easily diagnosed in its preclinical phase. This work aims at highlighting the complex though promising rationale for the use of selected micronutrients against age-related cognitive impairment and its progression. The advances made in the last decades in both defining the etiopathogenesis of cognitive impairment and in rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Studies in human beings have also found some correlation between markers of oxidative stress and cognitive function (97,98). The ability to modulate a decline in cognitive function with dietary supplements has met with mixed success, and this may be attributable in part to the complexity of cognitive assessment, differences in study design, efficacy of the antioxidants in question, and the difficulty of effectively delivering antioxidants to the brain (99). While the results in human trials are not conclusive, aged C57Bl6 mice treated with catalytic antioxidants maintain their cognitive function better than that of untreated mice (100).…”
Section: Sod2 In Agingmentioning
confidence: 99%
“…Studies in human beings have also found some correlation between markers of oxidative stress and cognitive function (97,98). The ability to modulate a decline in cognitive function with dietary supplements has met with mixed success, and this may be attributable in part to the complexity of cognitive assessment, differences in study design, efficacy of the antioxidants in question, and the difficulty of effectively delivering antioxidants to the brain (99). While the results in human trials are not conclusive, aged C57Bl6 mice treated with catalytic antioxidants maintain their cognitive function better than that of untreated mice (100).…”
Section: Sod2 In Agingmentioning
confidence: 99%
“…Indeed, supplementation with ascorbate, α-tocopherol, or both, have failed to produce conspicuous benefit in patients with neurodegenerative diseases such as PD and Alzheimer’s disease (AD) [103–107], although several conflicting lines of evidence have been reported [108–110]. In addition, it was reported that the levels of ascorbate and α-tocopherol in the CNS did not change in patients with PD and AD, compared with controls [27,28,101,111].…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
“…Nutrition rich in fruit and vegetables is beneficial to human health and wellbeing [ 1 , 2 , 3 , 4 ]. Secondary plant components, such as antioxidants [ 5 ], protect the cells and connective tissue against the development of oxidative stress, which is related to several pathological consequences, e.g., neurological [ 6 ], cardio-vascular [ 7 ], dermatological diseases [ 8 ] or aging [ 9 ]. Oxidative stress is induced by various factors, inter alia, solar radiation, smoking, alcohol consumption, lack of sleep, intensive physical activities and psychological stress [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and therefore cannot be avoided in daily life.…”
Section: Introductionmentioning
confidence: 99%